Kepemimpinan Transformasional Kepala Sekolah Dalam Meningkatkan Mutu Kinerja Guru: Studi Meta Analisis - Permatasari, Futika; Agus Lestari, Nia; Dewi Yulia Christie, Chitra; Suhaimi, Imam (JOM, 2023)
This study aims to explore in depth the role of principals' transformational leadership in improving the quality of teacher performance in the school environment. A meta-analysis method was used with a qualitative approach to investigate the findings of a number of articles published between 2017 and 2023. The ten articles analyzed revealed various aspects that highlighted the important role of principals in this context. The results of the analysis showed that principals act as leaders who not only manage the school administration, but also become prime movers in creating an environment that supports the growth and superior performance of teachers. They act as mentors, supervisors, innovators, and motivators for the teaching staff. As mentors, they provide direction, guidance, and support to teachers to improve their quality of teaching and learning. As supervisors, they monitor and evaluate the teaching and learning processes and provide constructive feedback for teachers' professional development. In addition, principals also act as innovators who formulate policy strategies to improve the quality of teacher performance in the entire school community. They motivate all personnel to achieve school goals by appreciating achievements, paying attention to individual needs, and creating a conducive work climate. In carrying out managerial tasks, principals also ensure the smooth running of all administrative activities, so that teachers' focus can remain on the learning process. The implication is that the transformational leadership of school principals has a significant impact on improving teacher performance and quality of education in schools. Through their various roles, principals shape an environment that supports, motivates, and inspires the teaching staff to achieve superior performance.